Hierarchical microstructure changes and the molecular mechanism of polypropylene under a critical failure strain during creep. (12th June 2015) - Jia, Chenfei; Zhang, Qiongwen; Liao, Xia; Zhu, Jingjun; Wu, Lingyun; Ni, Kai; Yang, Qi; An, Zhu; Li, Guangxian
Abstract: The hierarchical microstructure evolution of polypropylene during creep was explored via various methods, such as differential scanning calorimetry (DSC), scanning electron microscope (SEM), two-dimensional small-angle X-ray scattering (2D-SAXS), two-dimensional wide angle X-ray diffraction (2D-WAXD) and positron annihilation lifetime spectroscopy (PALS). The results revealed a correlation among the changes of micron-scale spherulites, nano-scale lamellae, crystalline blocks, atomic scale free volume and the deformation of polypropylene during creep. The elongation of micron-scale spherulites along the creep direction, accompanying with the increase of nano-scale lamellar long spacing, as well as the enlargement and amalgamation of atomic scale free volume were observed at ε below 17%; the imperfect fibrillar crystallites with polymer chains preferentially oriented along the creep direction, formed in the stress-induced crystalline block disaggregation–recrystallization process, were proved by SEM and 2D-SAXS results when ε was between 17% and 55%; the further orientation of polypropylene chains led to a higher degree of orientation and crystallinity. The molecular deformation mechanism of polypropylene during creep included three stages: the intralamellar slipping of crystalline blocks, accompanying with the enlargement and amalgamation of free volume, was activated at small strain ( ε ≤ 17%); whereas the stress-induced crystalline block disaggregation–recrystallization process as well as the rearrangement and orientation of chains were proceeded at medium strain (17% < ε ≤ 55%); at last, orientation-induced crystallization occurred at larger strain ( ε > 55%). Graphical abstract: Highlights: The molecular deformation mechanism of polypropylene during creep including three stages is proposed. The mechanism explains the transition point during creep deformation. Positron annihilation lifetime spectroscopy is a powerful microanalytical technique to explore the microstructure changes. The disaggregation–recrystallization process would lead the free volume to increase in number while decrease in size.